2018
DOI: 10.3390/jcm7060127
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personality Traits on the Severity of Alcohol Use Disorders

Abstract: Introduction: Alcohol Use Disorders (AUD) are the most prevalent psychiatric diagnosis in the general population. The study of personality characteristics, using Cloninger Personality Inventory (TCI-R), allows us to know the evolution of these patients at the beginning of treatment. Material and Method: We conducted a cross-sectional, observational and descriptive study for 3 years with a total of 304 patients. We studied the severity of their alcohol disorder by the Alcohol Dependency Intensity Scale (EIDA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Harm-avoidant temperament and impulsivity are well-known risk factors of PSU and other addictive disorders [ 12 , 42 , 57 , 58 ]. These risk factors may act as biological vulnerabilities to PSU.…”
Section: Discussionmentioning
confidence: 99%
“…Harm-avoidant temperament and impulsivity are well-known risk factors of PSU and other addictive disorders [ 12 , 42 , 57 , 58 ]. These risk factors may act as biological vulnerabilities to PSU.…”
Section: Discussionmentioning
confidence: 99%
“…According to Cloninger, gender influences the severity of alcohol consumption disorder via personality. Three of four temperamental variables (Reward Dependency, Avoidance of Damage and Search for Novelty) are influenced by gender in their relationship with severity of AUD [23]. These variations in results of present and previous studies with respect to personality profile and its correlation with severity of ADS could be attributed to differences in study population; sampling factors; characteristics of the sample; diagnostic criteria applied, or assessment procedures used.…”
Section: Discussionmentioning
confidence: 53%
“…Donadon and Osorio showed that alcoholic group scored lower on personality traits such as openness, agreeableness, conscientiousness, extraversion and neuroticism using Five personality factor inventory NEO revised [36]. In another study by Alvarez, et al, AUD patients suffered from more impulsive personality, have tendency to experience new emotions, apprehensive or more fearful, attributes their problems to others and may have lack of objectives [23].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations